Detection and dynamics of tumor necrosis factor alpha in the diagnosis and treatment of canine heartworm disease - Spasojević Kosić, Ljubica; Vracar, Vuk; Kozoderovic, Gordana; Lalosevic, Vesna (Veterinaria Italiana, 2024)
The aim of this study was to determine the concentration of TNF-alpha (TNF-α) in dogs naturally infected with Dirofilaria immitis (D. immitis) and to assess whether there are any changes in TNF-α concentration and their dependence during therapy for heartworm disease (HWD). For this study, 14 client-owned dogs with HWD were selected. Clinical and parasitological examinations (modified Knott test for circulating microfilariae and SNAP Test IDEXX for circulating D. immitis antigen) had been used for diagnosing D. immitis and HWD. All dogs were treated with an alternative therapy for HWD (oral doxycycline 10 mg/kg b.w., once daily for 6 weeks, then alternately 4 weeks without and 2 weeks with the medication, and oral ivermectin 6-14 µg/kg b.w., every 2 weeks). The dogs blood sera at the moment of HWD diagnosis, during and at the end of therapy were frozen for further quantifying of TNF-α (Canine TNF-alpha ELISA kit, Thermo scientific). At the moment of HWD diagnosis TNF-α was detected in 9 dogs (7.21±12.44 pg/ml). Concentration of TNF-α was not significantly change during the therapy, neither related to the level of D. immitis antigen nor to antigen level changes. The alternative therapy for HWD has no influence on TNF-α concentration dynamics.